The Role of Social Media in Communication Management of Non-Commercial Government Policy Campaigns Reviewed From the Public Information Disclosure Act - Ni Putu Sinta Dewi; Muhammad Fathoni; I Made Agus Artana; I Gede Anjas Kharismanata (Jurnal Manajemen, Informatika, Rekayasa Perangkat Lunak dan Teknologi Komunikasi, 2026)
This study examines the role of social media in the communication management of non-commercial government policy campaigns using the framework of Law Number 14 of 2008 concerning Public Information Disclosure. Non-commercial government policy campaigns are a form of public communication aimed at socializing regulations, programs, or state policies without a profit motive, and are oriented more toward increasing public awareness, participation, and transparency. The growing number of social media users in Indonesia year by year presents both opportunities and challenges for public bodies in managing policy communication effectively. A descriptive qualitative method was applied through library research techniques and document analysis of government policies, regulations, and social media communication practices. The findings show that social media plays a strategic role in strengthening transparency, accelerating information dissemination, and building two-way dialogue between government and society, although its use in practice is still dominated by one-way (push) communication patterns, so that public participation has not yet become fully meaningful. The implementation of the Public Information Disclosure Act through Information and Documentation Management Officers provides the legal framework underlying the management of non-commercial campaigns so that they remain transparent and accountable. This study reinforces the need for an adaptive, collaborative, and data-based digital communication strategy to optimize the role of social media in government policy campaigns, while also strengthening the institutional capacity of those who manage them.